Public spending in developing countries: trends, determination, and impact - Fan, Shenggen; Rao, Neetha (International Food Policy Research Institute, 2003)
The objective of this paper is to review trends in government expenditures in the developing world, to analyze the causes of change, and to develop an analytical framework for determining the differential impacts of various government expenditures on economic growth. Contrary to common belief, it is found that structural adjustment programs increased the size of government spending, but not all sectors received equal treatment. As a share of total government spending, expenditures on agriculture, education, and infrastructure in Africa; on agricultural and health in Asia; and on education and infrastructure in Latin America, all declined as a result of the structural adjustment programs. The impact of various types of government spending on economic growth is mixed. In Africa, government spending on agriculture and health was particularly strong in promoting economic growth. Asia's investments in agriculture, education, and defense had positive growth-promoting effects. However, all types of government spending except health were statistically insignificant in Latin America. Structural adjustment programs promoted growth in Asia and Latin America, but not in Africa. Growth in agricultural production is most crucial for poverty alleviation in rural areas. Agricultural spending, irrigation, education, and roads all contributed strongly to this growth. Disaggregating total agricultural expenditures into research and non-research spending reveals that research had a much larger impact on productivity than non-research spending.